HUBUNGAN DEMOGRAFI DENGAN PERILAKU MENGELUH PELANGGAN TELEPON SELULER DI KOTA DENPASAR - Dewi, Ika Candra; Nurcaya, I Nyoman (E-Jurnal Manajemen; Vol 4 No 1 (2015), 2015)
The purpose of this study was to determine the demographic relationship consists of age, gender, education level, and income level of the behavior complained of cellular phone subscribers in the city of Denpasar. This study uses qualitative research is by using questionnaires to 100 respondents. The data analysis technique used in this study were chi-square test of independence. It was found that age has a real connection with the conduct complained of. Furthermore, gender has a real connection with the conduct complained of. The level of education has a real connection with the conduct complained of. Income levels have a real relationship with the complaining behavior.
Keywords: Usia; Jenis Kelamin; Tingkat Pendidikan; Tingkat Pendapatan; Perilaku Mengeluh